Concentration assessment and source evaluation of 16 priority polycyclic aromatic hydrocarbons in soils from selected vehicle-parks in southern Nigeria - Onoriode O. Emoyan; Ejecha O. Onocha; Godswill O. Tesi (Scientific African, 2020)
The objectives of this study are to determine the concentrations and evaluate the sources of 16-priority polycyclic aromatic hydrocarbons (PAHs) in soils from selected vehicle-parks in southern Nigeria. The collection of soil samples was by soil auger from three sites at top (0–15 cm) and sub (15–30 cm) soil levels. Some soil physicochemical parameters were determined. Gas chromatography equipped with flame ionization detector (GC-FID was used to determine the concentrations of PAHs. The wet season concentrations of ∑16 PAHs range from 365.8 to 1065.8 µg/kg and 142.9 to 5321.9 µg/kg for top and sub soils, respectively, while the dry season concentrations of the ∑16 PAHs range from 66.4 to 269.3 µg/kg and 212.1 to 1342.5 µg/kg for top and sub soils, respectively. There was significant seasonal variation (p < 0.05) in the concentrations of PAHs in this study. Analyses of variance also show significant variation (p < 0.05) in the PAHs concentrations among the sites in wet and dry seasons. The concentration distribution of PAHs in this study also varied significantly (p < 0.05) with reference to season and soil depth. Isomer pair ratio shows that the principal source of PAHs is pyrogenic mostly from emission from vehicular traffic, and combustion from diesel, wood, coal and fossil fuels. Keywords: PAHs soil, Concentrations, Source evaluation, Vehicle-parks, Niger delta